Business Adaptation Strategies to External Environmental Changes in Indonesia: A Systematic Literature Review - Muh. Rizal Suyuti; Syarifuddin Syarifuddin; Alifia Ainun Rizky (Jurnal Administrasi Bisnis, 2026)
Changes in the external environment marked by globalization, digitalization, and technological disruption have increased complexity and uncertainty in the business world, necessitating organizations to develop effective and sustainable adaptation strategies. This research aims to identify, analyze, and synthesize business adaptation strategies to external environmental changes in Indonesia using the Systematic Literature Review (SLR) approach. The research method refers to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure transparency and systematicity in the literature selection process. Data were obtained from the Scopus, ScienceDirect, Google Scholar, and Garuda databases with a publication range from 2020 to 2025.Research results show that business adaptation strategies in Indonesia predominantly encompass four main dimensions, namely digital transformation, business model innovation, strengthening organizational capabilities based on dynamic capabilities, and collaboration within the business ecosystem. Digital transformation has proven to enhance operational efficiency and market access, while business model innovation enables companies to create more adaptive added value. Organizational capabilities play a role in enhancing responsiveness to change, while ecosystem collaboration expands access to resources and business opportunities. However, the implementation of these strategies still faces various obstacles, such as the digital divide, limited human resources, and suboptimal regulatory support. This research produces a conceptual model of business adaptation that integrates external environmental factors, adaptation processes, and outputs in the form of increased competitiveness and business sustainability. Theoretically, this research enriches the literature on business adaptation strategies in the context of developing countries, while practically providing implications for the formulation of more adaptive policies and business strategies in Indonesia.